Effective Situational Diagnosis : A Programmed Learning Text Based on the 3-D Theory - Bélanger, Laurent (Relations industrielles / Industrial Relations, 1975)
This article reviews "Effective Situational Diagnosis : A Programmed Learning Text Based on the 3-D Theory" by W.J. Reddin and R. Stuart-Kotze.
Keywords: SnR_publicationTitle_Relations industrielles_Relations industrielles / Industrial Relations_2025-09-22T15:31:55.974Z